Histomorphological, Micrometrical and Histochemical Characteristics of Abomasum in Gaddi Sheep (Ovis aries) - Malik, Shabir Ahmad; Rajput, Rajesh; Farooq , Uiase Bin; Rafiq , Mohd (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present study was conducted to know the histoarchitecture and histochemical characteristics of abomasum of adult Gaddi sheep (n=6). Lamina propria of the tunica mucosa was occupied by cardiac, fundic and pyloric glands. Lamina epithelialis consisted of tall columnar epithelial cells. The number of chief cells was greater compared to parietal cells in the gastric glands and showed basophilic reaction. However parietal cells were comparatively larger than chief cells or mucous neck cells and showed strong eosinophilic reaction. Fundic glands were simple tubular whereas pyloric glands were simple, straight, branched tubular glands which opened into the gastric pits. Depth of gastric pits in the pyloric region was higher than in cardiac and fundic regions. The predominant cells of pyloric glands were the mucous neck cells. Tunica submucosa was composed of a network of collagen, reticular and elastic fibres. Tunica muscularis was composed of an inner circular and outer longitudinal layer. Histochemical reactions were mainly demonstrated in surface epithelium, gastric pit epithelium and gastric gland cells of abomasum. Abundant acid mucopolysaccharides were localized in the pyloric region of abomasum which indicated the predominance of mucous neck cells in pyloric region.
Keywords: Gaddi; Abomasum; Histology; Histochemistry; Chief cells; Parietal cells; Mucous neck cells